Assessment of embodied energy of masonry building materials in Hassan, India. (2023) - Devanand, R.; Prashanth, S.; Devi, Pinky L; Chethan, B.A.; Amar, R.; Harsha, H.N.
Abstract: The construction sector is putting a lot of effort in reducing its energy, carbon, material, and water footprints, as well as taking steps toward a more sustainable built future. The building materials such as cement, aggregates, masonry units like bricks and blocks constitute to dominant percentile utilization in the construction of building. The activities involved in the production of construction materials will consume large amounts of energy. Hence time has arrived for an effective, environmental friendly, sustainable building material with judicious use of energy. It is therefore important to identify and modify the existing process of manufacture of building construction materials and compute the energy associated with manufacturing process. Production of these materials is a major cause for global warming due to release of carbon-di-oxide (CO2 ) and other gases. Hence there is a need to think, act and adopt low energy consuming, locally available building materials, reducing the transportation energy (TE) to provide alternatives which is both cost effective and environment friendly. The whole energy expenditure involved in the material manufacturing, including all upstream activities such as raw material extraction and transportation, is referred to as embodied energy (EE). This paper examines the energy efficiency of a few masonry building materials used in large quantities in the Indian construction sector. The key stages of production, consumption of excessive energy and the importance locally available raw materials are studied. The study focuses on the various stages of production and measuring the associated embodied energy of masonry building materials of Hassan. These EE figures were calculated by personal visits and survey data to industrial production plants. EE of burnt brick masonry is found to be 2.8 times the EE in comparison with AAC block masonry wall.